Legal Consequences Of Incomplete Delivery of Information in Medical Checkups Where The Treadmill Test Was Not Conducted Due To Medical Reasons: Akibat Hukum Ketidaklengkapan Informasi Pada Medical Checkup Yang Treadmill Testnya Tidak Terlaksana Dengan Alasan Medis - Hafidz Nur; Sumiyati, Yeti; Titik; Mufidi, Faiz; Wagiono, Caecielia (LITIGASI, 2025)
The Medical Checkup (MCU) service that includes a treadmill test facility is a routine health examination designed to identify potential cardiovascular diseases, implemented using the Bruce Protocol method as Standard Operating Procedures (SOP) and Hospital Practice Guidelines to conduct the treadmill test. The legal basis for this medical service outlined in Indonesian Ministry of Health Decree Number 772/Menkes/SK/VI/2002 and Indonesian Ministry of Health Regulation Number 512/Menkes/PER/IV/2007. The treadmill test has risks and contraindications, which means that not all patients may be able to undergo the treadmill test procedure in the MCU package. This study will explore the legal implications of incomplete information during medical checkups in cases of MCU package services which treadmill test facilities cannot be carried out due to patient's medical condition. Consumer Protection Law Number 8 of 1999 and Article 1320 of the Civil Code will serve as the foundation for analyzing therapeutic contracts. The research method which used in this study is normative juridical approach which is supported by interveiw data. The Results of this study found that when a treadmill test cannot be performed due to patients' medical condition, the patient unable to undergo the procedure, , resulting in legal consequences in form of financial loss which may causes potential disputes if not handled properly. This incident cannot be considered as as breach of contract because the hospital has fulfilled its obligations by providing information and asking for approval through informed consent, so the hospital is not required to reimburse the patient. However, it is...